Safety Assessment of Sudden Water Pollution in Lanzhou Section of Yellow River Based on Matter-Element Extension Model - Cui Wenxiang; Jin Chunling; Gong Li; Liu Jingjing; Su Yang (Shuitu baochi tongbao)
[Objective] The safety level of sudden water pollution in the Yellow River basin was scientifically evaluated in order to provide a reference for improving the emergency response capacity to a sudden water pollution incident in the Yellow River. [Methods] Based on the principles of science, integrity, and data availability, 16 indicators related to the Lanzhou section of the Yellow River were selected through the PSR model to construct an evaluation index system. Based on the data of the Lanzhou section of the Yellow River from 2014 to 2019, the index weight was determined by GRA-PCA combination, and the matter-element extension model was used to obtain the safety evaluation level of sudden water pollution. [Results] The safety level of sudden water pollution in the Lanzhou section of the Yellow River was level Ⅱ (major hazard) in 2014; level Ⅰ (particularly major hazard) in 2016; level Ⅲ (greater hazard) in 2015, 2017—2019. The overall trend of decreasing from level Ⅱ (major hazard) to level Ⅲ (larger hazard) was basically consistent with the effect observed by the government of Gansu Province on the Yellow River in recent years. [Conclusion] The GRA-PCA matter-element extension evaluation model method was reasonable and operable. It can accurately evaluate the safety level of sudden water pollution in the Lanzhou section of the Yellow River, and also provide a reference for the evaluation of sudden water pollution safety levels in other river basins.